2020
DOI: 10.1002/jeab.583
|View full text |Cite
|
Sign up to set email alerts
|

Matching theory and induction explain operant performance

Abstract: Matching theory is a general framework for understanding allocation of behavior among activities. It applies to choice in concurrent schedules and was extended to single schedules by assuming that other unrecorded behavior competes with operant behavior. Baum and Davison (2014) found that the competing activities apparently are induced by the “reinforcers” (phylogenetically important events, e.g., food) according to power functions. Combined with power‐function induction, matching theory provides new equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 50 publications
(135 reference statements)
4
31
0
Order By: Relevance
“…), are the first ones to validate power‐function induction of operant activities directly. Up to now, the evidence for power‐function induction was indirect: the choice relations conforming to Equation 10 and accounts of response rate that were otherwise infeasible (Baum, ; Baum & Davison, ; Baum & Grace, ). This evidence was consistent with power‐function induction as an assumption but failed to demonstrate it as an actuality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), are the first ones to validate power‐function induction of operant activities directly. Up to now, the evidence for power‐function induction was indirect: the choice relations conforming to Equation 10 and accounts of response rate that were otherwise infeasible (Baum, ; Baum & Davison, ; Baum & Grace, ). This evidence was consistent with power‐function induction as an assumption but failed to demonstrate it as an actuality.…”
Section: Discussionmentioning
confidence: 99%
“…The coefficient c may account for differing units, depending on the physical characteristics of the activity. Baum () used power‐function induction to account for key pecking on single VI schedules (also Baum & Grace, ). Baum and Davison () suggested that power‐function induction, as determining competitive weight, ought to be included in the matching relation.…”
mentioning
confidence: 99%
“…The word “contiguous” means just closeness in time, and the assumption about contiguous reinforcers caused Skinner (1948) to claim incorrectly that noncontingent presentation of food must strengthen some behavior—whatever it was contiguous with. Subsequent research has shown that noncontingent food induces food‐related activities (e.g., Baum & Aparicio, 2020; Baum & Grace, 2020; Segal, 1972; Staddon & Simmelhag, 1971). Moreover, subsequent research showed that response–reinforcer contiguity is neither necessary nor sufficient for favored activities to be selected (e.g., Baum, 1973; Kuroda & Lattal, 2018; Rescorla, 1967, 1968, 1988).…”
Section: Molar and Molecular Paradigmsmentioning
confidence: 99%
“…Performance in experiments with mixed contingent and noncontingent food sheds light also on the Law of Induction and the Law of Covariance (Baum, 2018a(Baum, , 2018bBaum & Aparicio, 2020). The general concept of induction introduced by Segal (1972) becomes specific in quantitative accounts as power functions relating responding to rate of food delivery (Baum, 2015;Baum & Davison, 2014;Baum & Grace, 2020).…”
mentioning
confidence: 99%
“…Noncontingent food presented concurrently with contingent food typically reduces operant activity (Dickinson & Charnock, 1985;Lattal, 1974;Rescorla, 1992;Schachtman & Reed, 1990), because according to the Law of Allocation, induced nonoperant activity competes with the operant activity. Noncontingent food may also induce formerly operant activity no longer in covariance with it, at least for a time (e.g., Baum & Grace, 2020;Herrnstein, 1966;Reid, 1958;Rescorla & Skucy, 1969). In a molar view of operant behavior, covariance occurs between responsecontingent food rate and response rate and may be represented by feedback functions within a behavior-environment feedback system (Baum, 1981(Baum, , 1989(Baum, , 2020.…”
mentioning
confidence: 99%